Οι Ουνίτες στην Τουρκία και στην Ελλάδα - Macar, Elcin (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2004)
A religious movement known under the name of «Uniates», i.e.: groups of Greek Catholics holding Byzantine rite, started its activity in Istanbul as early as the second half of the XIX century. At the same time Bulgarian Uniates started their activity in Macedonia. Towards the end of the second half of the XIX century, minor groups of Greek Uniates started to consolidate their churches in Malkara (Tekirdag) and Gallipoli. These small-sized religious communities consisted basically of a number of families scattered all over the region. Although running parallel, the two movements went through a quite different development in their respective countries. As a matter of fact, whilethe Bulgarian Uniates grew in importance as the number of their followers increased, their Greek counterpart did not seem either to thrive or to exparid in Istanbul. During the period of the exchange of populations between Greece and Turkey (1923), the majority of Istanbul’s community and the entire communities of Malkara and Gallipoli chose to migrate to Greece with their clerics. Over the past seventy years the community of Uniates still existing in Istanbul has gradually become smaller and smaller, which made it unnecessary for their parishes and worship establishments to be kept open. As a consequence, since 1996 the few parishioners have started joining Latin Catholic churches for religious ceremonies owing to the fact that the last Uniate priest died in that year. Since then the community has been under the jurisdiction of the Apostolic Vicar of Istanbul.